Private Forests and Private Forest Legislation - Augier, P. W. (Indian Forester, 1952)
The account stresses the unsuitability of the Indian Forest Act of 1927 to cope with the destruction of the private protected forests, and as in Bihar most of the forested areas (some 80 per cent) are under zamindars as opposed to the balance (20 per cent) under Government, it was fitting that this State should be the first to move in the matter of taking them over. Some differences between the Indian Forest Act on the one hand and the Bihar Private Forests Acts of 1946 and 1947 on the other are shown and then again the differences between the latter, two the first being certified by the Governor and the second passing through the legislature. The destruction or at least the serious damage wrought to the forests as soon as the application of the Act was sensed in certain quarters, is indicated. When the Act was first applied, only a certain number of staff to help in the preliminary work of demarcation, was sought and sanctioned. The heavy inroads on the forests in the preliminary stages could not be foreseen, and valuable time was lost in obtaining full control. The paper states that the work of demarcation is complete, that there has been a beginning at scientific management and the destruction is under control. Other States contemplating this work would do well to avoid pit-falls of the Private Forest Act and to have a staff adequate to take over from the very beginning.